2018
DOI: 10.1016/j.rmcr.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis patient supported with extracorporeal membrane oxygenation for 403 days while waiting for a lung transplant: A case report

Abstract: According to the Extracorporeal Life Support Organization, the average duration of veno-venous extracorporeal membrane oxygenation (V-V ECMO) in adults with acute respiratory failure is 10.5–13.5 days. Some patients on V-V ECMO may not recover in such a short period of time, and recently, there have been more reports of prolonged V-V ECMO. However, we do not know how long it is feasible to wait for native lung recovery or lung transplant (LTx) with the use of ECMO. We describe a patient with acute exacerbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The ELSO registry data showed that 4,361 adult patients who underwent prolonged ECMO for respiratory failure had a mean ECMO duration of 22 days ( 10 ). Moreover, previous cases demonstrated that prolonged ECMO support for 265 days without complications was possible; one patient received ECMO for 403 days while waiting for lung transplantation but died soon after decannulation ( 11 , 12 ). In our case, VV-ECMO was maintained for 111 days and successful weaning and recovery of lung function was achieved in a patient with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The ELSO registry data showed that 4,361 adult patients who underwent prolonged ECMO for respiratory failure had a mean ECMO duration of 22 days ( 10 ). Moreover, previous cases demonstrated that prolonged ECMO support for 265 days without complications was possible; one patient received ECMO for 403 days while waiting for lung transplantation but died soon after decannulation ( 11 , 12 ). In our case, VV-ECMO was maintained for 111 days and successful weaning and recovery of lung function was achieved in a patient with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are situations where extensive pulmonary fibrosis is present, but gas exchange is not severely altered and patients do not experience severe restrictions. If this satisfactory lung function at baseline is worsened by acute infection, this situation could/should represent a relative contraindication in individual cases [ 50 , 51 ]. Unfortunately, no guidance is available on the extent of fibrosis still “acceptable” to initiate ECMO treatment, while the mode of rating the extent of fibrosis remains ambiguous.…”
Section: Absolute Contraindications To the Initiation Of Ecmomentioning
confidence: 99%
“…However, this therapy may be extended if the primary cause of respiratory failure necessitating ECMO is expected to resolve and there have been cases where ECMO supports were continued for more than 2 weeks. 14,15 Also if lung transplant facility is available and feasible, in case the lungs did not improve on ECMO therapy, then longer ECMO run can be considered, provided the other vital organ (brain, kidney, and liver) functions are preserved and the patient is well treated for the pulmonary infection.…”
Section: Discussionmentioning
confidence: 99%
“…14 Umei et al had their experience of 403 days long ECMO run for idiopathic pulmonary fibrosis while waiting for a lung transplant. 15 Kim et al described a 107 days ECMO run for interstitial pneumonia as a bridge to lung transplant. 19 Raza et al reported a 300 days ECMO run for severe fibrotic lung disease.…”
Section: Discussionmentioning
confidence: 99%